Hope on the inside [large type] - Bostwick, Marie (Center Point Large Print, 2019)
"Hope Carpenter finds new purpose in a new phase of life when her husband's forced retirement strains both their savings and their marriage. Seeking inspiration and a financial boost, Hope gets a job teaching crafts to inmates at a local women's prison with surprising results"--